KUALITAS PELAYANAN PUBLIK DI KUA BANDUNG WETAN, KOTA BANDUNG DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN POTENTIAL GAIN IN CUSTOMER VALUE (PGCV) - Syahrial Sidik; Wahyuari, Wahyuari; Supriyadi Sapolo; M. Nasyubun; Anisha Maharani Tambunan (Journal of Innovation Research and Knowledge, 2025)
The quality of public services is an important factor in building public trust in government institutions, including the Office of Religious Affairs (KUA). This study aims to analyze the quality of public services at the KUA Bandung Wetan, Bandung City, using the Importance Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV) methods. The IPA method is used to identify gaps between the level of importance and service performance based on public perception, while PGCV is used to measure the potential for service value improvement by identifying attributes that significantly impact customer satisfaction. This study employs a descriptive quantitative approach with a questionnaire distributed to 46 respondents. The IPA analysis results indicate two indicators that should be prioritized for improvement: Timeliness (KW2) and Transparency of Procedures (TP1), as they have high importance values but suboptimal performance. The PGCV calculations confirm that improvements in these two indicators have the potential to significantly enhance the perceived value of services by the public. This study contributes theoretically by integrating the IPA and PGCV approaches in public service evaluation based on ServQual, and practically by providing strategic improvement recommendations for KUA to sustainably enhance public satisfaction.